Durability aspects of additive manufactured parts for advanced requirements - Rechtenwald, Thomas; Frick, Thomas; Schmidt, Michael; Schüßler, Florian; Rösch, Michael; Hörber, Johannes; Feldmann, Klaus (Zeitschrift Kunststofftechnik, 2010)
Additive fabrication technology is predominantly used for prototyping applications up to now. One reason why these flexible technologies are not widely used for end user products is the restricted knowledge about the durability of the manufactured parts. This work provides detailed data on the long term behaviour of mechanical properties of stereolithography specimens after accelerated aging by thermal shock cycling according to automotive standards. One stereolithography resin is found, which shows high durability under repeated extreme thermal load.<br